(untitled) (Balthazar, 2025)
Susan Sontag’s interest in visual research, documented by numerous essays, is closely linked to the central role that the author has recognized in the photographic gaze, in understanding a series of cognitive and social processes in modern capitalist societies. Her approach has highlighted, over a period ranging from the early Seventies to the early 2000s, a series of effects of construction and deconstruction in the formation of common sense, linking them to the settlement of forms of social intimacy with the photographic medium. Sontag’s long-standing interest in the history of photography, and in the evolution of consumer practices related to this medium, testifies to the political engine of her research: recognizing the principles of construction of social reality between representation, power of fiction and information overload, developing a critical understanding of capitalist society through the traffic of images that innervates it.